Semiotics in the Lyrics of the Song “Kun Anta” by Humood Al-Khuder - Dita Permata Yadiyanti (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2021)
In this research "Semiotics in Kun Anta's Song Lyrics popularized by Humood Al-Khuder" uses a qualitative method, with a corpus of Arabic song lyrics Kun Anta. The purpose of this research is to find out the form of phrases or sentences that contain semiotic meanings in the song lyrics, and to find out the deeper meanings contained therein.The theory used is Charles Sanders Pierce's semiotic theory in which Pierce categorizes the triangle of meaning theory which consists of three main elements, namely, signs, objects, and interpretants. In this study too, the researcher concluded that the lyrics of the kun anta song have deep meaning from the semiotic aspect so that lessons can be learned from the song lyrics.